Rediscovery of Mantellias pubicornis Westwood, 1889, a rare praying mantis from the Amazon (Mantodea, Thespidae, Oligonicinae) - Maldaner, Caroline; Agudelo, Antonio A.; Rafael, José Albertino (Zootaxa, 2015)
Many praying mantis species remain known from type specimens only. The majority of these taxa have vague taxonomic limits, as original descriptions are often very short, making strong emphasis on superficial characters (Rivera 2010). One clear example of this is the Amazonian Mantellias Westwood, 1889, a monotypical genus represented by Mantellias pubicornis Westwood, 1889.